Numerical and Experimental Studies on Combustion Engines and Vehicles - Woś, Paweł; Jakubowski, Mirosław (IntechOpen, 2020)
The matters discussed and presented in the chapters of this book cover a wide spectrum of topics and research methods commonly used in the field of engine combustion technology and vehicle functional systems. This book contains the results of both computational analyses and experimental studies on jet and reciprocating combustion engines as well heavy-duty onroad vehicles. Special attention is devoted to research and measures toward preventing the emission of harmful exhaust components, reducing fuel consumption or using unconventional methods of engine fueling or using renewable and alternative fuels in different applications. Some technical improvements in design and control of vehicle systems are also presented.